2012
DOI: 10.1021/bm201663f
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Modulate the Switch among Different States of the Hydrophobin Vmh2 from Pleurotus ostreatus

Abstract: Fungal hydrophobins are amphipathic, highly surface-active, and self-assembling proteins. The class I hydrophobin Vmh2 from the basidiomycete fungus Pleurotus ostreatus seems to be the most hydrophobic hydrophobin characterized so far. Structural and functional properties of the protein as a function of the environmental conditions have been determined. At least three distinct phenomena can occur, being modulated by the environmental conditions: (1) when the pH increases or in the presence of Ca(2+) ions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…It is evident that the ␤-sheet structure is always dominant. It has been previously demonstrated that pH increase by NH 3 addition leads to amyloid-like fibrils formation in Vmh2 solutions [15]. FT-IR deconvolution analysis of B2 and B4 in comparison with B1 and B3 samples, respectively, shows a decrease of ␣-helical, as expected, and an increase of ␤-turn contribution, rather than ␤-sheet, phenomenon usually ascribed to an increase of disorder.…”
Section: Analysis Of the Coating Conditionssupporting
confidence: 72%
See 2 more Smart Citations
“…It is evident that the ␤-sheet structure is always dominant. It has been previously demonstrated that pH increase by NH 3 addition leads to amyloid-like fibrils formation in Vmh2 solutions [15]. FT-IR deconvolution analysis of B2 and B4 in comparison with B1 and B3 samples, respectively, shows a decrease of ␣-helical, as expected, and an increase of ␤-turn contribution, rather than ␤-sheet, phenomenon usually ascribed to an increase of disorder.…”
Section: Analysis Of the Coating Conditionssupporting
confidence: 72%
“…Since the obtained value for amide content are related to the average on the whole membrane surface analyzed, this result can be due to a more uniform and homogeneous distribution of the protein samples slowly dried at room temperature with respect to that quickly dried at 60 • C. On the other hand, when the pH was increased by adding NH 3 (B2, B4), the obtained values of amide content were very similar, independently from the drying temperature. In this case the layer formation process was mainly triggered by the pH change leading to a quick aggregation, as previously demonstrated [15]. Moreover the B6 samples prepared in 20% ethanol and dried at room temperature are characterized by the highest amide content, the lowest lipid/amide ratio and a carbohydrate/amide ratio with an intermediate value among the ones shown in Table 3.…”
Section: Analysis Of the Coating Conditionssupporting
confidence: 62%
See 1 more Smart Citation
“…7 Unfortunately, since the crystalline model of HFB is not yet available, the interaction between protein and sugars is not completely understood: from biological consideration, HFB is not a sugar binding protein, so that the presence of a specific binding site cannot be hypothesized, but it selectively binds glucose with respect to other sugars, 28 at least in solutions. One of the aims of this work is to verify if the selfassembled biolayer of hydrophobins is still able to interact with glucose.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that apart from the primary sequence, environmental factors like tertiary contacts within the folded protein, solvent polarity, ions, pH, temperature etc. have also been considered to be of great significance in determining the conformational preference of a sequence [5,6]. Studies have shown that upon decreasing the solvent polarity an α-to 3 10 -helix conformational switching occurs, as in the case of an acylated heptapep tide amide comprising six C α -tetrasubstituted amino acids and one histidine [7] and an amphiphilic peptide of the triacylglycerol lipase derived from Pseudomonas aeruginosa [8].…”
Section: Introductionmentioning
confidence: 99%